Aripiprazole for relapse prevention and craving in alcohol use disorder: current evidence and future perspectives. (2nd June 2016) - Martinotti, Giovanni; Orsolini, Laura; Fornaro, Michele; Vecchiotti, Roberta; De Berardis, Domenico; Iasevoli, Felice; Torrens, Marta; Di Giannantonio, Massimo
ABSTRACT: Introduction : Among other approaches, the modulation of the dopaminergic pathway has been advocated in the therapeutic management of Alcohol Use Disorders (AUD). A potential avenue toward the modulation of the dopaminergic pathway across varying substance disorders seems to be provided by aripiprazole, a second-generation antipsychotic characterized by a peculiar pharmacodynamics signature. Areas covered : In this review, the authors provided a qualitative synthesis and a critical perspective on the efficacy of aripiprazole in relapse prevention and craving in AUD. A systematic search was carried out through MEDLINE/Embase/PsycINFO/Cochrane Library from inception until September 2015, combining free terms and MESH headings for the topics of AUD and aripiprazole as following: ((( Alcohol use Disorder ) OR ( Alcohol use)) AND aripiprazole ). Expert opinion : Based both on a qualitative synthesis and a critical interpretation of the evidence, the authors submit that aripiprazole would promote alcohol abstinence and reduce the alcohol seeking behaviour possibly via dopaminergic and serotoninergic modulations at the fronto-subcortical circuits underpinning alcohol reward and craving, impulsive behaviour as well as reduce alcohol-related anxiety/low mood and anhedonia. However, due to the lack of published studies, a conclusive statement about any direct effect of aripiprazole in the prevention of craving and/or alcohol consumption is not possible.